Returning to Nothing: The Lost of Malay Settlement in Pasir Mas, Kelantan. - Abdullah, Azli Bin; Wahid, Julaihi Bin (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2022)
Natural calamities such as earthquakes, landslides, windstorms, and floods are considered disasters according to the degree of disruption they caused to the human population, built environment, or natural ecosystem. Natural disasters are a common occurrence in rural settlements of Malaysia, affecting the lives of the rural population and damaging the rural settlements, agriculture, roads, drainage schemes, and other infrastructure. This threat continues to exist, and disasters are still wreaking havoc in rural areas. However, this disaster is compounded by the current rate of urbanization in the region. Human life conjures a spatial location due to the unique combination of movement and strength that characterizes humans. Humans, unlike trees, are not stationary; yet they require more manmade shelters than other animals, and communities. Humans, in particular, share their space. A loss narrative defines today's place literature: specifically, the loss of the correct link between place and meaning (Cox, 1968; Lynch, 1972; Jacobs & Appleyard, 1987; Kunstler, 1993). Simultaneously, this article aims to investigate the disappearance of Malay settlements and discuss some of the implications. In February 2021. a landslide event took place in Pasir Mas, Kelantan. It is an area where researchers used to spend their youth. The objective of this article is to provide a perspective on the disappearance of Malay settlement by studying two theories, namely natural calamity and Malay settlement. The entire idea of this article is the transformation of the components of place characterized by the narrative of loss has enormous planning and design implications, two of which are central here: firstly, the emergence of geographies of place, and secondly, the loss of Malay culture crisis.